PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU SMP NEGERI NEGERI DI KECAMATAN KAMPAR KABUPATEN KAMPAR - Raisah Al Atiyah; Isjoni Isjoni; Sumardi Sumardi (Universitas Riau, 2017)
The purpose of this study was to determine the effect of compensation on jobsatisfaction, the work environment on job satisfaction, and also the compensation and workenvironment on job satisfaction at Junior High Schools (SMPN) In Kampar District Kampar,This reaserch uses data collection techniques questionnaire and analyzed using multiple regressionvariables The study consisted of two independent variables that compensation (X1) and workenvironment (X2) while the dependent variable is the Teacher Job Satisfaction (Y). The studypopulation was a teacher SMPN districts of Kampar regency Kampar amounted to 108 peopleand 85 samples.Research shows that that there is significant influence compensation and workenvironment simultaneously on teacher job satisfaction of 0,754 or 75,4% and the partialcorrelation coefficient compensation to work on teacher job satisfaction of 0,291 which meansthat 29,1% of the variation strengthening or weakening the performance of a teacher determinedby the compensation to work. The correlation coefficient between work environment on teacherjob satisfaction of 0,731 which means that 73,1% of the variation strengthening and weakeningof teacher job satisfaction is determined by work environment.